Martyrology, a (Pseudo-)historical Source: the case of Prudentius’ Hymn in Honour of the St. Quirinus - Pobežin, Gregor (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
This paper deals with the historical value of martyrologies, such as Eugippus’ vita of St. Severinus and especially the poetic transcript of a fourth-century martyrology, the vita of St. Quirinus. Both saints were horrifically executed but later faced a similar fate: their bodies were exhumed and transferred to Italy, and their relics scattered all over the towns of the North Adriatic.